2016
DOI: 10.1080/15384101.2016.1234552
|View full text |Cite
|
Sign up to set email alerts
|

A new layer of degradation mechanism for PR-Set7/Set8 during cell cycle

Abstract: Set8 is critically involved in transcription regulation, cell cycle progression and genomic stability. -dependent Set8 destruction also contributes to the tight control of cell proliferation and cell cycle progression, in response to UV irradiation. Here, we summarize our new findings regarding the crucial role of b-TRCP in CKI-mediated Set8 degradation, which could provide new evidence to support that dysregulation of a tight regulatory network of Set8 could lead to aberrant cell cycle process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 90 publications
(117 reference statements)
0
4
0
Order By: Relevance
“…Protein ubiquitination and deubiquitination are involved in the regulation of virtually all aspects of cellular biology, with effects ranging from altered protein stability to changes in protein function. Several E3 ligases have been reported to promote the ubiquitination and degradation of SET8 (7). In contrast, the DUB(s) of SET8 require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Protein ubiquitination and deubiquitination are involved in the regulation of virtually all aspects of cellular biology, with effects ranging from altered protein stability to changes in protein function. Several E3 ligases have been reported to promote the ubiquitination and degradation of SET8 (7). In contrast, the DUB(s) of SET8 require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…SET8 protein expression is tightly regulated during the cell cycle, and SET8 homozygous null mutant embryos displayed early lethality due to cell-cycle defects and improper mitotic chromosome condensation, reflecting its essential roles in the proper progression of the cell cycle 22 . The dysregulation of SET8 expression has been implicated in many disease conditions, including cancer 22,23 . SET8 overexpression has been detected in various types of tumors and associated with the poor survival rate of cancer patients [24][25][26] .…”
Section: Set8 Is a Novel Negative Regulator Of Tgf-β Signaling In A M...mentioning
confidence: 99%
“…As consequence, G1/S transition is blocked and the cell cycle stopped [ 69 ]. In MCF7 and MDA-MB231 breast cancer cell lines, USP17 knockdown also led to a decrease in SET (Su(var)3-9, enhancer of zeste and trithorax) domain-containing protein 8 (SET8) levels, resulting in the suppression of cell proliferation due to the increase in p21 levels [ 68 , 70 ]. Another study demonstrated that ectopic expression of USP17 in HEK293T cells led to deubiquitination of the ELK1 transcription factor that is involved in ERK (extracellular-signal-regulated kinase) signaling.…”
Section: Association Of Ubiquitin-specific Proteases (Usps) With Cancer-related Processesmentioning
confidence: 99%